Power plant instrumentation and control handbook : a guide to thermal power plants - Basu, Swapan; Debnath, Ajay Kumar; Books24x7, Inc. (London: Elsevier, 2015)
This book discusses instrumentation and control in modern fossil fuel power plants, with an emphasis on selecting the most appropriate systems subject to constraints engineers have for their projects. It provides all the plant process and design details, including specification sheets and standards currently followed in the plant. Features of the book are the inclusion of control loop strategies and BMS/FSSS step by step logic; coverage of analytical instruments and technologies for pollution and energy savings; and coverage of the trends toward filed bus systems and integration of subsystems into one network with the help of embedded controllers and OPC interfaces; includes comprehensive listings of operating values and ranges of parameters for temperature, pressure, flow, level, etc of a typical 250/500 MW thermal power plant. --
0
Includes bibliographical references and index.
Keywords: Geothermal power plants -- Handbooks, manuals, etc; Power-plants -- Handbooks, manuals, etc; Fossil fuel power plants -- Handbooks, manuals, etc; Electronic books; Electronic books